2022
DOI: 10.1002/ldr.4428
|View full text |Cite
|
Sign up to set email alerts
|

Towards sustainable and efficient land development: Risk of soil heavy metal(loid)s in abandoned gold mines with short‐term rehabilitation and potential value for targeted remediation

Abstract: Recently sustainable and efficient land development and the potential reutilization values of abandoned mines (i.e., industrial, arable, and tourism) have been attracting worldwide attention. However, environmental impacts after rehabilitation practices are often ignored and field data are lacking. What remains unknown is an understanding how the risk of soil trace metal(loid)s (TMs) respond to short-term rehabilitation of abandoned gold mines and the potential value for following targeted remediation. We foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…Similarly, Berasaluce et al (2019) and Salmani-Ghabeshi et al (2016) found similar results. In the latter study, arsenic ingestion through accidental ingestion of soil and house dust in localities close to the VIC was identified to pose a carcinogenic risk on infants (1-5 years), which contrasts with other contamination cases (e.g., Cao et al, 2022). In addition to environmental assessments, the studies by Madrid et al (2022Madrid et al ( , 2023 concluded that environmental pollution in Quintero and Puchuncaví localities has induced epigenetic changes in the genome and oxidative stress on DNA of its inhabitants, with arsenic being the primary contaminant.…”
mentioning
confidence: 92%
“…Similarly, Berasaluce et al (2019) and Salmani-Ghabeshi et al (2016) found similar results. In the latter study, arsenic ingestion through accidental ingestion of soil and house dust in localities close to the VIC was identified to pose a carcinogenic risk on infants (1-5 years), which contrasts with other contamination cases (e.g., Cao et al, 2022). In addition to environmental assessments, the studies by Madrid et al (2022Madrid et al ( , 2023 concluded that environmental pollution in Quintero and Puchuncaví localities has induced epigenetic changes in the genome and oxidative stress on DNA of its inhabitants, with arsenic being the primary contaminant.…”
mentioning
confidence: 92%
“…The spatial resources and landscape conditions of the abandoned mine site are extremely rich, with good design and transformation basis. How to carry out landscape transformation of the abandoned mine site in the background of the "post-industrial era" on the basis of this design, how to deal with the large number of land destroyed due to underground mining, arable land erosion rate reduced by a series of ecological and environmental damages is a serious challenge facing the present [4][5][6].…”
Section: Introductionmentioning
confidence: 99%